2016
DOI: 10.1055/s-0035-1565238
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of the Three-minute All-out Test for Non-motorized Treadmill Tethered Running

Abstract: The 3-min all-out test was developed and validated on a cycle ergometer using a modification of a linear mathematical equation (1/time vs. power) obtained from the original critical power model. The purpose of this development was to obtain, in a single test, the aerobic and anaerobic capacity parameters and identify the exercise transition moment from heavy to severe intensity. The aim of this study was to propose an adaptation of the all-out 3-min cycle ergometer to a non-motorized treadmill with tethered ru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0
3

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(26 citation statements)
references
References 31 publications
0
23
0
3
Order By: Relevance
“…The AO30 evaluations were performed on the NMT previously described [22][23][24][25]. The acquisition system consisted of a strain gauge (CSA / ZL-500 MK Control, Sao Paulo, Brazil), a portable amplifier (MKTC5-10, MK Control, Sao Paulo, Brazil) and an acquisition module (NI USB-6009, National Instruments, Austin, EUA).…”
Section: All-out 30-s Tethered Running Testmentioning
confidence: 99%
See 1 more Smart Citation
“…The AO30 evaluations were performed on the NMT previously described [22][23][24][25]. The acquisition system consisted of a strain gauge (CSA / ZL-500 MK Control, Sao Paulo, Brazil), a portable amplifier (MKTC5-10, MK Control, Sao Paulo, Brazil) and an acquisition module (NI USB-6009, National Instruments, Austin, EUA).…”
Section: All-out 30-s Tethered Running Testmentioning
confidence: 99%
“…Since futsal players constantly perform running efforts, a non-motorized treadmill tethered running ergometer (NMT) could provide substantial parameters for these athletes, and has not yet been applied. This ergometer has proved to be highly sensitive to determine force, velocity and power under high-frequency acquisition (1000 Hz) [22][23][24][25]. Recently, Zagatto, et al [23] adopted the all-out 30-second test (AO30) and indicated significant associations among the mechanical parameters from NMT within the anaerobic capacity, proving the importance of such an ergometer on physiological evaluations.…”
Section: Introductionmentioning
confidence: 99%
“…In this model, the aerobic capacity is called EP (end power), and the W’ is called WEP. The original 3MT application [ 4 ] was performed on a cycle ergometer, and its reproducibility was confirmed by several authors on different ergometers [ 5 , 6 , 7 ]. The 3MT has already been applied as a critical velocity predictor in free running [ 2 , 8 ], and the reliability of this test using measurements of tethered running power output on a non-motorized treadmill (NMT) has been recently demonstrated [ 7 ].…”
Section: Introductionmentioning
confidence: 98%
“…Mechanical power-based physical assessments in the specific movement of running are important in sports because they provide mechanical performance data that enables to determine the work (Ԏ) executed and allows physiological measures of energy expenditure during exercise [ 9 , 10 ]. Furthermore, power output measure can be an essential tool to determine the individual potential of runners since it reflects a complete mechanical efficiency parameter–athletes who run faster using less force save energy outlay [ 7 , 9 ]. In most sports that include running exercises, power output parameters are required to prescribe training, since their performance is a result of the muscle’s ability to respond as fast as it can, showing that running power plays a decisive role in several competitions, both in individual and team sports.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation